Inhibitors of the renin-angiotensin system in experiment hypertension, with a note on the measurement of angiotensin I, II and III during infusion of converting-enzyme inhibitor - Morton, J. J. (1979)
1 Prolonged infusion (11 h) of both saralasin and angiotensin-converting enzyme inhibitor (SQ20881) gradually lowered BP in two-kidney hypertensive rats to levels similar to that in normotensive rats infused with dextrose. 2 Saralasin did not lower BP in DOCA-salt-hypertensive rats. 3 These observations support the notion that in chronic renal hypertension, angiotensin II may maintain hypertension by a slowly developing action. 4 Plasma angiotensin II in rats infused with SQ20881 was suppressed relative to renin, but was not eliminated. 5 Chromatography of angiotensin II extracts from dogs infused with converting enzyme inhibitor (SQ14,225) showed that the very high levels of angiotensin I achieved after treatment with SQ14,225 can lead to falsely high estimated angiotensin II levels as a result of angiotensin I cross-reacting with the angiotensin II assay.